Covid, work-from-home, and securities misconduct - Douglas J. Cumming; Christopher Firth; John Gathergood; Neil Stewart (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
We consider whether traders are more likely to commit securities violations when trading at home, a new form of working induced by the Covid pandemic. We examine data pre- and post-Covid, during which some traders were unexpectedly forced to work at home. The data indicate the presence of both a treatment and a selection effect, where work at home exhibits fewer misconduct cases. Work at home is associated with fewer cases of trading misconduct, although no difference in communications misconduct. The economic significance of working from home on trading misconduct is large for both the treatment and selection effects.
Keywords: G12; G14; G18; K22; 330; Market Manipulation; Trading; Surveillance; Securities Regulation